The first main group ureilite with primary plagioclase: A missing link in the differentiation of the ureilite parent body. (4th August 2022) - Goodrich, Cyrena A.; Collinet, Max; Treiman, Allan; Prissel, Tabb C.; Patzek, Markus; Ebert, Samuel; Jercinovic, Michael J.; Bischoff, Addi; Pack, Andreas; Barrat, Jean‐Alix; Decker, Stephan
Abstract: MS‐MU‐012, a 15.5 g clast from the Almahata Sitta polymict ureilite, is the first known plagioclase‐bearing main group ureilite. It is a coarse‐grained (up to 4 mm), equilibrated assemblage of 52% olivine (Fo 88), 13% orthopyroxene (Mg# 89.2, Wo 4.5), 11% augite (Mg# 90.2, Wo 37.3), and 14% plagioclase (An 68), plus minor metal and sulfide. The plagioclase grains have been secondarily remelted and internally recrystallized, but retain primary external morphologies. Melt inclusions occur in olivine. Rounded chadocrysts of olivine and orthopyroxene are enclosed in augite grains. In terms of texture, mineralogy, major and minor element mineral compositions, and oxygen isotopes, MS‐MU‐012 is virtually identical to the archetypal Hughes‐type main group ureilites, with the significant addition of primary plagioclase. We conclude that MS‐MU‐012 formed as a cumulate in a common lithologic unit with the Hughes‐type ureilites. Based on reconstructed compositions of melts trapped in olivine, orthopyroxene, and augite in the Hughes‐type samples, we infer that the parent magma of the Hughes unit originated as a late melt in the incremental melting of the ureilite parent body (UPB), near the end of the melting sequence, but was not completely extracted from the mantle like earlier melts and was emplaced in an intrusive body. MELTS calculations indicate that olivine began to crystallize at 1260 °C, followed shortly thereafter by co‐crystallization of orthopyroxene and augite. Plagioclase began to crystallize at 1170–1180 °C. Graphite was buoyant in the melt and became heterogeneously distributed in flotation cumulates. Residual silicate liquid was extracted from the cumulate pile and could have crystallized to form the "labradoritic melt lithology" (with plagioclase of An 68‐35), which is partially preserved as clasts in polymict ureilites. The final equilibration temperature recorded by the Hughes unit was 1140–1170 °C, just before catastrophic disruption of the UPB. MS‐MU‐012 provides a critical missing link in the differentiation history of this asteroid.